Inter-Subunit Dynamics Controls Tunnel Formation During the Oxygenation Process in Hemocyanin Hexamers - Bux, Khair; Shen, Xiayu; Tariq, Muhammad; Yin, Junqi; Moin, Syed Tarique; Bhowmik, Debsindhu; Haider, Shozeb (Frontiers in Molecular Biosciences, 2021)
Hemocyanin from horseshoe crab in its active form is a homo-hexameric protein. It exists in open and closed conformations when transitioning between deoxygenated and oxygenated states. Here, we present a detailed dynamic atomistic investigation of the oxygenated and deoxygenated states of the hexameric hemocyanin using explicit solvent molecular dynamics simulations. We focus on the variation in solvent cavities and formation of tunnels in the two conformational states. By employing principal components analysis and CVAE-based deep learning, we are able to differentiate between the dynamics of the Deoxy- and Oxygenated states of hemocyanin. Finally, our results identify the deoxygenated open conformation, which adopts a stable, closed conformation after the oxygenation process.